(untitled) (Qawanin Jurnal Ilmu Hukum, 2025)
This study aims to determine and analyze the Effectiveness of Electronic Trial Implementation at the Makassar State Administrative Court and to determine and analyze the Factors that Influence the Effectiveness of Electronic Trial Implementation at the Makassar State Administrative Court. In this study, legal regulations and the reality in the field will be analyzed to provide answers to the questions raised. This study uses an empirical legal research method, with the research location in Makassar City and its location at the Makassar State Administrative Court. Data were collected through interview techniques and literature studies, which were then analyzed descriptively analytically. The results of the study indicate that the Effectiveness of the Implementation of Supreme Court Regulation Number 1 of 2019 Concerning Electronic Case Administration and Trials in Court (Case Study at the Makassar State Administrative Court) has not been fully effective because there are still many obstacles that hinder the implementation of electronic trials. Coupled with the settlement of cases from year to year experiencing fluctuating data. This is due to one of the factors that greatly influences, among others, the infrastructure factor, namely the network which still often experiences disruptions. As a recommendation, In order to improve the effectiveness of the implementation of electronic trials at the Makassar State Administrative Court in accordance with the Supreme Court Regulation with the intent and purpose of the government, it is necessary to add and update facilities and infrastructure, especially those related to the network. The government also needs to hold special training for judges and advocates so that law enforcers become more professional and the government needs to conduct socialization to the public about the importance of technology at this time. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis Efektivitas Pelaksanaan Persidangan Secara Elektronik di Pengadilan Tata Usaha Negara Makasaar dan untuk mengetahui dan menganalisis Faktor-faktor yang memengaruhi Efektivitas Pelaksanaan Persidangan Secara Elektronik di Pengadilan Tata Usaha Negara Makassar. Di dalam penelitian ini peraturan hukum dan kenyataan di lapangan akan dianalisis untuk memberikan jawaban atas persoalan yang diajukan. Penelitian ini menggunakan metode penelitian hukum empiris, dengan lokasi penelitian di Kota Makassar dan tempatnya di Pengadilan Tata Usaha Negara Makassar. Data dikumpulkan melalui teknik wawancara dan studi Pustaka, yang kemudian dianalisis secara deskriptif analitis. Hasil penelitian menunjukkan bahwa Efektivitas Pelaksanaan Peraturan Mahkamah Agung Nomor 1 Tahun 2019 Tentang Administrasi Perkara Dan Persidangan Di Pengadilan Secara Elektronik (Studi Kasus Pada Pengadilan Tata Usaha Negara Makassar) belum sepenuhnya efektif di karenakan masih banyak kendala yang menghambat jalannya persidangan elektronik. Ditambah dengan penyelesaiaan perkara dari tahun ke tahun mengalami data yang fluktuatif. Hal ini disebabkan salah satu faktor yang sangat mempengaruhi antara lain faktor sarana prasarana yaitu jaringan yang masih sering mengalami gangguan. Sebagai rekomendasi, Dalam rangka meningkatkan efektivitas pelaksanaan persidangan elektronik di Pengadilan Tata Usaha Negara Makassar agar sesuai dengan Peraturan Mahkamah Agung dengan maksud dan tujuan pemerintah perlu menambah dan memperbaharui sarana dan prasarana tertutama yang berkaitan dengan jaringan. Pemerintah juga perlu mengadakan pelatihan khusus kepada hakim dan advokat agar penegak hukum menjadi lebih professional serta pemerintah perlu melakukan sosialisasi kepada masyarakat akan pentingnya teknologi pada saat ini.